2238. Immunogenicity and safety of four- vs. three-standard doses HBV vaccination in HIV-infected adults with isolated anti-HBc antibody. (26th November 2018) - Laksananun, Nattinee; Chaiwarith, Romanee
Abstract: Background: HIV-infected patients have decreased serological response to HBV vaccination with faster decline of protective antibody (Ab) titer. In those with isolated anti-HBc Ab, the role of vaccination remains controversial. We, therefore, conducted this study aimed to determine immunogenicity and safety of four- vs. three-standard doses HBV vaccination in HIV-infected adults with isolated anti-HBc antibody. Methods: An open-label randomized controlled trial with 1:1 allocation was conducted among HIV-infected patients attending the Infectious Diseases clinic of the Maharaj Nakorn Chiang Mai Hospital, Faculty of Medicine Chiang Mai University, Chiang Mai, Thailand between July and September 2017. Eligibility participants must be ≥18 years old, taking cART, CD4 ≥200 cells/mm 3, HIV VL < 20 copies/mL, and positive isolated anti-HBc Ab. The participants were randomized to receive either three-standard-doses (20 µg at Months 0, 1, 6) or four-standard-doses (20 µg at Months 0, 1, 2, 6) IM HBV vaccination and were evaluated for anamnestic response at Week 4 after the first dose and response at Week 28. Predictive factors for anamnestic response and vaccine responders at Week 28 were analyzed. Results: Of the total of 97 patients screened, 54 participants were enrolled and randomized. Thirty-two participants were male (59.3%) with the mean age of 46 years old. Anamnestic response occurred in 25.9% vs. 33.3% in three doses vs. four doses arm respectively ( P = 0.551). After vaccination, the response rates at Week 28 were 85.2% in three doses arm vs. 88.9% in four doses arm ( P = 1.000); with 44.4% vs. 63.0% being high-level responders, respectively ( P = 0.172). GMT of anti-HBs Ab at Week 28 in three doses arm and four doses arm were 63.8 and 209.8 mIU/mL, respectively, P = 0.030. No adverse events were reported. A younger age (<45 years old) and higher nadir CD4 count (≥100 cells/mm 3 ) were independently predictive factors of anamnestic response with the odd ratio (OR) of 17.4 (95% CI 3.0–102.0) and 21.6 (95% CI 2.7–170.4) respectively. No predictive factors of responders at Week 28 were found. Conclusion: In Thai HIV-infected patients with isolated anti-HBc Ab, anamnestic response occurred considerably with both regimens, but the majority was still unprotected. Hence, a single dose vaccination is insufficient. The usual three-standard-doses vaccination was highly effective with high response rate. Disclosures: All authors: No reported disclosures.